Molecular Basis for Defining the Pineal Gland and Pinealocytes as Targets for Tumor Necrosis Factor - Carvalho-Sousa, Cláudia E.; da Silveira Cruz-Machado, Sanseray; Tamura, Eduardo K.; C. M. Fernandes, Pedro A.; Pinato, Luciana; Muxel, Sandra M.; Cecon, Erika; Markus, Regina P. (Frontiers in Endocrinology, 2011)
The pineal gland, which is the gland that translates darkness into an endocrine signal by releasing melatonin at night, is now considered a key player in the mounting of an innate immune response. Tumor necrosis factor (TNF), the first pro-inflammatory cytokine to be released by an inflammatory response, suppresses the translation of the key enzyme of melatonin synthesis (arylalkylamine-N-acetyltransferase-alkyl-N-acetyltransferase, Aa-nat). Here we show that TNF receptors of the subtype 1 (TNF-R1) are expressed by astrocytes, microglia and pinealocytes. We also show that the activation of TNF triggers the nuclear factor kappa B (NFKB) pathway in pinealocytes by reducing the cytoplasmic level of the inhibitory nuclear factor kappa B protein of the subtype A (NFKBIA). The TNF-induced nuclear translocation of the p50/p50 NFKB transcription factor lacks a transactivation domain, and this phenomenon explains how TNF blocks the transcription of Aa-nat. In addition, the p65/RelA nuclear translocation was read-out following the expression of inducible nitric oxide synthase (iNOS) and the synthesis of nitric oxide NO. The increase in the transcription of genes activated by NFKB opens a new perspective for understanding the implication of the pineal gland in pathophysiological conditions.